Safety of One-Stage Reconstruction of Achilles Tendon and Soft Tissue Defects Resulting from Infection After Achilles Tendon Repair using Flexor Hallucis Longus Tendon Transfer and Reverse Sural Artery Flap - Lee, Jae Hoon; Ku, KiHyeok; Kang, Chang Min; D'Lima, Darryl D; Baek, Jong Hun (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2025)
Infection after Achilles tendon (AT) repair can lead to defects in both the tendon and the surrounding soft tissue. In such cases, a two-stage surgical approach is generally adopted, with soft tissue reconstruction performed initially, followed by secondary tendon reconstruction. A reverse sural artery flap (RSAF) after AT repair is not commonly performed due to potential damage to the flap pedicle. This study aims to evaluate the clinical outcomes of simultaneous flexor hallucis longus tendon (FHLT) transfer and RSAF to treat soft tissue and tendon defects resulting from infection after AT repair.We reviewed 20 patients who had undergone one-stage reconstruction of AT and soft tissue defects resulting from infection after AT repair using FHLT transfer and RSAF between October 2012 and October 2022, with a minimum of a 1-year postsurgical follow-up. Surgical outcomes were assessed based on the success of the flap, recurrence of infection, and tendon re-rupture. Clinical evaluation included visual analog scale (VAS) score, ankle range of motion, and patient-reported components of the American Orthopaedic Foot and Ankle Society (AOFAS) score (maximum of 68 points).All flaps were successful. The mean size of the flap was 7.2×4.1 cm2. There was no recurrence of infection or tendon re-rupture. The mean VAS and AOFAS scores were 0.5 and 64.6, respectively. The mean ankle joint range of motion was 13.5° for dorsiflexion and 35° for plantar flexion.One-stage reconstruction with FHLT transfer and RSAF is a safe and effective surgical method in patients with tendon and soft tissue defects after AT repair.
Keywords: flexor hallucis longus tendon transfer; reverse sural artery flap; infection; one-stage reconstruction